2018
DOI: 10.3389/fped.2018.00084
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Output Monitoring in Preterm Infants

Abstract: Maintaining optimal circulatory status is a key component of preterm neonatal care. Low-cardiac output (CO) in the preterm neonate leads to inadequate perfusion of vital organs and has been linked to a variety of adverse outcomes with heightened acute morbidity and mortality and adverse neurodevelopmental outcomes. Having technology available to monitor CO allows us to detect low-output states and potentially intervene to mitigate the unwanted effects of reduced organ perfusion. There are many technologies ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 107 publications
0
17
0
1
Order By: Relevance
“…Cutting the umbilical cord eliminates the low-resistance placental flow and stimulates peripheral and central chemoreceptors, which combined with other factors (thermal, neuroendocrine, and mechanical stimuli), contributes to the onset and maintenance of neonatal respiratory efforts. A subsequent increase in SVR and reduction in right heart preload results [6], with the SVR continuing to increase due to cold stress and catecholamine surges [76]. Initiation of breathing stimulates a series of events that are responsible for the shift from fetal to postnatal circulatory patterns.…”
Section: Neonatal Structural Adaptations: Neonatal Circulation and Momentioning
confidence: 99%
“…Cutting the umbilical cord eliminates the low-resistance placental flow and stimulates peripheral and central chemoreceptors, which combined with other factors (thermal, neuroendocrine, and mechanical stimuli), contributes to the onset and maintenance of neonatal respiratory efforts. A subsequent increase in SVR and reduction in right heart preload results [6], with the SVR continuing to increase due to cold stress and catecholamine surges [76]. Initiation of breathing stimulates a series of events that are responsible for the shift from fetal to postnatal circulatory patterns.…”
Section: Neonatal Structural Adaptations: Neonatal Circulation and Momentioning
confidence: 99%
“…Maintenance of cardiac output is a key predictor of sepsis survival in infants and children and an important therapeutic target. [51][52][53] Additionally, we found that M3 was able to increase left ventricular end diastolic diameter, a characteristic that has also been associated with increased survival. [54,55] As such, we postulated that the myocardial dysfunction in sepsis was due, in part, to eCIRP.…”
Section: Discussionmentioning
confidence: 51%
“…Treatment of septic mouse pups with M3 resulted in an improvement in CO. Maintenance of cardiac output is a key predictor of sepsis survival in infants and children and an important therapeutic target (Weiss 2020;Davis 2017;McGovern and Miletin 2018). Additionally, we found that M3 was able to increase left ventricular end diastolic diameter, a characteristic that has also been associated with increased survival (Huang et al 2013;Furian 2012).…”
Section: Global Longitudinal and Radial Strain Declines Following Expmentioning
confidence: 60%